Characterization of H7 influenza A virus in wild and domestic birds in Korea. - Hyun-Mi Kang; Ha-Young Park; Kyu-Jun Lee; Jun-Gu Choi; Eun-Kyoung Lee; Byung-Min Song; Hee-Soo Lee; Youn-Jeong Lee (PLoS ONE)
During surveillance programs in Korea between January 2006 and March 2011, 31 H7 avian influenza viruses were isolated from wild birds and domestic ducks and genetically characterized using large-scale sequence data. All Korean H7 viruses belonged to the Eurasian lineage, which showed substantial genetic diversity, in particular in the wild birds. The Korean H7 viruses from poultry were closely related to those of wild birds. Interestingly, two viruses originating in domestic ducks in our study had the same gene constellations in all segment genes as viruses originating in wild birds. The Korean H7 isolates contained avian-type receptors (Q226 and G228), no NA stalk deletion (positions 69-73), no C-terminal deletion (positions 218-230) in NS1, and no substitutions in PB2-627, PB1-368, and M2-31, compared with H7N9 viruses. In pathogenicity experiments, none of the Korean H7 isolates tested induced clinical signs in domestic ducks or mice. Furthermore, while they replicated poorly, with low titers (10⁰·⁷⁻¹·³ EID₅₀/50 µl) in domestic ducks, all five viruses replicated well (up to 7-10 dpi, 10⁰·⁷⁻⁴·³EID₅₀/50 µl) in the lungs of mice, without prior adaptation. Our results suggest that domestic Korean viruses were transferred directly from wild birds through at least two independent introductions. Our data did not indicate that wild birds carried poultry viruses between Korea and China, but rather, that wild-type H7 viruses were introduced several times into different poultry populations in eastern Asia.